2011
DOI: 10.1103/physreve.83.031604
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized nanopatterns in thin layers of superheated liquid metals

Abstract: In this paper experimental observations of self-organized patterns in resolidified thin films of liquid superheated metals are reported. The superheated melt layers represent an example of a system driven far from equilibrium, which undergoes explosive boiling and solidifies afterward. The melts appear in the course of single-shot femtosecond laser heating of metal samples. Self-organized cells, solitonlike structures, periodic stripes, and transient patterns are observed. Pattern properties and mechanisms lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 20 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…These remnants form the random relief in Figure 1D. This solid relief is observed in experiments in vacuum [23][24][25][26][27][28] and in the case of ablation in liquid, see Figure 8 in [7].…”
Section: Decay Of Metal Into Vacuum or Liquidmentioning
confidence: 55%
“…These remnants form the random relief in Figure 1D. This solid relief is observed in experiments in vacuum [23][24][25][26][27][28] and in the case of ablation in liquid, see Figure 8 in [7].…”
Section: Decay Of Metal Into Vacuum or Liquidmentioning
confidence: 55%
“…Similarity between the patterns generated upon the laser ablation (cells [3,42], LIPSS) and the convection patterns [43] suggests that convection may be the physical reason of the LIPSS generation. Moreover, the patterns in these both systems are induced by heating of a thin liquid layer.…”
Section: Hydrodynamic Instabilitiesmentioning
confidence: 81%
“…That is, the excitation of the surface plasmons by reducing the phase velocity of light is not realized by laser ablation, since it requires an exact fitting the incident angle of the light to the optical constants of the material. The LIPSS appear at similar laser ablation parameters in metals, semiconductors, dielectrics and polymers [1,2,3,4,5,6,28], i.e., in conductive and in dielectric materials, which have a broad range of dielectric constants. This fact suggests that other ways of the plasmon excitation, independent on the material properties, must be looked for.…”
Section: Excitation Via Slow Lightmentioning
confidence: 98%
“…In this context, recent theoretical studies have shown that surface gradients of temperature may be sufficient to enable the development of surface hydrodynamic instabilities on metals and semiconductors [49,50], whereas non-dimensional number analysis has been proposed for laser-irradiated metals [51]. Although recent time-resolved imaging of laser-irradiated semiconductors could not strictly lead to the emergence of grating-like LIPSS after a single pulse [27], such a possibility was observed in specific laser-irradiated metals where LIPSS were seemingly originating from hydrodynamic effects [52]. To shed light on the laser-induced hydrodynamic phenomena under our experimental conditions, in the present study, a similar approach was applied to investigate the possible regimes of molten layer transport in the case of hot fused silica.…”
Section: Resultsmentioning
confidence: 99%